2003
DOI: 10.1287/mnsc.49.9.1268.16570
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mixed-Integer Programming Models for Nonconvex Piecewise Linear Cost Minimization Problems

Abstract: We study a generic minimization problem with separable non-convex piecewise linear costs, showing that the linear programming (LP) relaxation of three textbook mixed integer programming formulations each approximates the cost function by its lower convex envelope. We also show a relationship between this result and classical Lagrangian duality theory.Key words: piecewise-linear, integer programming, linear relaxation, Lagrangian relaxation. Resum6Nous considerons un probleme de minimisation gen6rique dans lequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 15 publications
2
100
0
Order By: Relevance
“…We tested three well-known linearizations of piecewise linear functions: multiple choice (MC), incremental formulations, and convex combination formulations (see, e.g., Croxton et al 2003 …”
Section: Computational Resultsmentioning
confidence: 99%
“…We tested three well-known linearizations of piecewise linear functions: multiple choice (MC), incremental formulations, and convex combination formulations (see, e.g., Croxton et al 2003 …”
Section: Computational Resultsmentioning
confidence: 99%
“…They can be solved with algorithms such as the one proposed by Keha et al [89], a branch-and-cut algorithm without auxiliary binary variables for solving non-convex separable piecewise linear optimization problems that uses cuts and applies SOS2 branching. They can also be modeled as mixed integer programming (MIP) problems, following the work shown by Croxton et al [90], where it was demonstrated that the linear programming relaxation of three textbook mixedinteger programming models for non-convex piecewise linear minimization problems are equivalent, each approximating the cost function with its lower convex envelope.…”
Section: Piecewise Linear Functions and Non-convex Optimizationmentioning
confidence: 99%
“…Extending this definition, Croxton et al [17] and Keha et al [18] define a locally ideal SOS2 formulation as one whose LP relaxation has extreme points that all satisfying the SOS2 property. As shown by Vielma et al [5], all commonly used MIP formulations of PLFs, except for the original convex combination (CC) model, are known to be locally ideal.…”
Section: Properties Of Mip Formulationsmentioning
confidence: 99%